Numerical investigation on fully-developed heat transfer augmentation and friction factor with dimple shaped intrusion and different radius of curvatures on triangular ducts. (25th February 2023) - Bharath Raju, L.B.; Sastry, G.R.K.; Gugulothu, S.K.; Kesava Reddy, K.; Deepanraj, B.
Highlights: The influence of dimple shaped intrusion and radius of curvature are explored. With the decrease in the Rc (from Rc = 0.67 h to 0.333 h), the flow near the corners increases. The average Nusselt number has growth from 5.71–44.37 %, 3.172–23.76 %, & 1.16–8.27 %for Rcs 0.333 h, 0.49 h & 0.56 h respectively. Friction factor is reduced from 79–45 %, 51–24 % & 26–7 % for Rcs 0.333 h, 0.49 h & 0.56 h respectively. Addition of dimple-shaped intrusion in the triangular duct with rounded corner, increases the heat transfer rate. Abstract: The heat transfer phenomenon is moderate in the case of triangular ducts due to the presence of sharp corners, which causes stagnant flow in the corners. Thus, this study focuses on improving heat transfer by converting one of the corners of the duct to a rounded structure having a variable curvature radius value (Rc). Rc varies from 0.67 h (maximum value) to 0.33 h (minimum value), where h is the height of the duct. Heat transfer and airflow have also been tested with dimple-shaped intrusion and rounded corners under varying ranges of relative length in the longitudinal direction (Z/e = 10–18) and relative length in the transverse direction (X/e = 10–18). Application of thermal-based boundary conditions on the turbulent flow for Re = 5600–21, 000 facilitates the heat transfer analysis in a duct under steady-state. The commercial software tool, ANSYS Fluent 18.1, is used to simplify-three dimensional Reynolds averaged Navier Stokes equation with the compressible fluid flow by considering the pressure-based solver with the standard K- ε turbulence model. Compared to a typical duct, the rounded corner area shows higher velocity because of the dimple intrusions and rounded corners. Introduction of curvature to the corner opposite to the heat-conducting surface in simple triangular duct results in the increment of heat transfer by 5.71–44.37 %, 3.172–23.76 %, and 1.16–8.27 % for the values of Rc = 0.33 h, 0.49 h, and 0.56 h, respectively. Further the addition of dimple-shaped intrusion in the triangular duct with rounded corner, increases the heat transfer for Z/e = X/e = 18 as visible from the increment in average Nusselt Number by 22.9–91.52 %, 49.41–129.82 %, 31.96–89.26 % and 14.36–85 % for Rc = 0.333 h, 0.49 h, 0.56 h & 0.67 h respectively for Re spanning from 5600 to 21000.